Mobility of plume-derived volcanogenic elements in meteoric water at Nyiragongo volcano (Congo) inferred from the chemical composition of single rainfall events - Liotta, Marcello; Bobrowski, Nicole (Geochimica et cosmochimica acta, 2017)
The chemical composition of single rainfall events was investigated at Nyiragongo volcano (Democratic Republic of Congo) with the aim of determining the relative contributions of plume-derived elements. The different locations of the sampling sites allowed both plume-affected samples (hereafter referred to as “fumigated samples”) and samples representative of the local background to be collected. The chemical composition of the local background reflects the peculiar geographic features of the area, being influenced by biomass burning, geogenic dust, and biological activity. Conversely, fumigated samples contain large amounts of volcanogenic elements that can be clearly distinguished from the local background. These elements are released into the atmosphere from the persistently boiling lava lake of the Nyiragongo crater and from the neonate lava lake of Nyamulagira. These emissions result in a volcanic plume that includes solid particles, acidic droplets, and gaseous species. The chemical signature of the volcanic emissions appears in falling raindrops as they interact with the plume. HCl and HBr readily dissolve in water, and so their ratio in rain samples reflects that of the volcanic plume. The transport of HF is mediated by the large amount of silicate particles generated at the magma-air interface. SO2 is partially converted into SO42− that dissolves in water. The refractory elements dissolved in rain samples derive from the dissolution of silicate particles, and most of them (Al, Mg, Ca, and Sr) are present at exactly the same molar ratios as in the rocks. In contrast, elements such as Na, K, Rb, Cu, and Pb are enriched relative to the whole-rock composition, suggesting that they are volatilized during magma degassing. After correcting for the dissolution of silicate particles, we can define that the volatility of the elements decreases in the following order: Pb≫Rb>K>Na. This finding, which is the first for a volcanic plume, is consistent with previous measurements in high-temperature fumaroles at other volcanic areas.